Propositional epistemic luck, epistemic risk, and epistemic justification - Bondy, Patrick; Pritchard, Duncan (Synthese (Dordrecht), 2018)
If a subject has a true belief, and she has good evidence for it, and there’s no evidence against it, why should it matter if she doesn’t believe on the basis of the good available evidence? After all, properly based beliefs are no likelier to be true than their corresponding improperly based beliefs, as long as the subject possesses the same good evidence in both cases. And yet it clearly does matter. The aim of this paper is to explain why, and in the process delineate a species of epistemic luck that has hitherto gone unnoticed—what we call propositional epistemic luck—but which we claim is crucial to accounting for the importance of proper basing. As we will see, in order to understand why this type of epistemic luck is malignant, we also need to reflect on the relationship between epistemic luck and epistemic risk.